2020
DOI: 10.1080/09523987.2020.1848512
|View full text |Cite
|
Sign up to set email alerts
|

Tensions and trade-offs of participatory learning in the age of machine learning

Abstract: While much has been written about the personal, social, and democratic benefits of networked communities and participatory learning, critics have begun to draw attention to the ubiquitous data collection and computational processes behind mass user platforms. Personal and behavioral data have become valuable material for statistical and machine learning techniques that have the potential to profile, infer, and predict people's needs, values, and behavior. As a response, researchers are calling for data literac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Resulting from our approach, we discovered that most of the reviewed papers of studies leaned towards teaching ML to high schoolers. Literature (Su & Yang, 2022) has shown that limited discussion exists about AI activities appropriate for younger children, however, studies have been carried out to introduce ML at early years of pupils' generation of ML knowledge (Druga et al, 2019;Vartiainen et al, 2020aVartiainen et al, , 2020b. Nevertheless, no basis could be identified to assume that high schools are the levels that requires ML knowledge, it is essential to conduct research on ML projects suitable for kindergarten, elementary and middle schools.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Resulting from our approach, we discovered that most of the reviewed papers of studies leaned towards teaching ML to high schoolers. Literature (Su & Yang, 2022) has shown that limited discussion exists about AI activities appropriate for younger children, however, studies have been carried out to introduce ML at early years of pupils' generation of ML knowledge (Druga et al, 2019;Vartiainen et al, 2020aVartiainen et al, , 2020b. Nevertheless, no basis could be identified to assume that high schools are the levels that requires ML knowledge, it is essential to conduct research on ML projects suitable for kindergarten, elementary and middle schools.…”
Section: Discussionmentioning
confidence: 99%
“…It can be deduced from the literature that ML has been taught across K-12 levels from primary to high school. These have also been carried out in various settings such as in laboratory (Essinger & Rosen, 2011), classroom (Chai et al, 2020), summer camp , workshop (e.g., Druga et al, 2019) and at home (Vartiainen et al, 2020a(Vartiainen et al, , 2020b. The objective of the identified studies focuses on how to teach central machine learning concepts with a paper (Vachovsky et al, 2016) concerned with increasing girls' interest in AI.…”
Section: Pedagogical Developmentmentioning
confidence: 99%
See 3 more Smart Citations